2003
DOI: 10.1007/s00424-003-1012-4
|View full text |Cite
|
Sign up to set email alerts
|

BK channel openers inhibit migration of human glioma cells

Abstract: Large-conductance Ca(2+)-activated K(+) channels (BK channels) are highly expressed in human glioma cells. However, less is known about their biological function in these cells. We used the patch-clamp technique to investigate activation properties of BK channels and time-lapse microscopy to evaluate the role of BK channel activation in migration of 1321N1 human glioma cells. In whole cells, internal perfusion with a solution containing 500 nM free Ca(2+) and external application of the BK channel opener phlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
56
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 24 publications
8
56
0
Order By: Relevance
“…In tumor cells, BK Ca channels regulate cell volume and shape and contribute to tumor progression and migration (3)(4)(5).…”
mentioning
confidence: 99%
“…In tumor cells, BK Ca channels regulate cell volume and shape and contribute to tumor progression and migration (3)(4)(5).…”
mentioning
confidence: 99%
“…Maxi-K channels are distributed in various tissues, such as human brain tumors, vascular smooth muscle cells, and endothelial cells, and their activations were shown to inhibit migration of human glioma cells (18). The maxi-K channels are synergistically regulated by various intracellular second messengers, such as cytoplasmic Ca 2ϩ concentration, cGMP, hydrogen peroxide, and nitric oxide (NO) (19 -21).…”
mentioning
confidence: 99%
“…Previous in vitro studies showed that disrupted BK channel functional activity inhibits glioma cell proliferation (33,34) and migration (35,36). Earlier, we showed that prolonged activation of BK channels of T9 or U251 gliomas in vitro causes cell swelling and eventually leads to paraptosis (7,8).…”
Section: Discussionmentioning
confidence: 91%